2006
DOI: 10.2495/afm06049
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of compressible transitional cascade flows

Abstract: The large eddy simulation (LES) of compressible transitional flows in a low-pressure turbine cascade is performed by using 6 th -order compact difference and 10 th -order filtering method. The numerical results without free-stream turbulence and those with about 5% of free-stream turbulence are compared. In these simulations, separated-flows in the turbine cascade accompanied by laminar-turbulent transition are realized, and the present results closely agree with past experimental measurements in terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…With the enormous development in computer science, the large eddy simulation (LES) method has been used in compressor cascade flow simulation in recent years, utilizing a large amount of computer resources (Matsuura & Kato, 2007;McMullan & Page, 2011;Teramoto, 2005;Zaki, Wissink, Durbin, & Rodi, 2009). Modeling threedimensional corner separation requires the CFD code to be very robust.…”
Section: Introductionmentioning
confidence: 99%
“…With the enormous development in computer science, the large eddy simulation (LES) method has been used in compressor cascade flow simulation in recent years, utilizing a large amount of computer resources (Matsuura & Kato, 2007;McMullan & Page, 2011;Teramoto, 2005;Zaki, Wissink, Durbin, & Rodi, 2009). Modeling threedimensional corner separation requires the CFD code to be very robust.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of this work, further efforts were made to improve turbulence modelling of the flow in turbomachinery [10]. The influence of freestream turbulence on transition on turbine blades has been investigated using LES [11], highlighting the need for reasonably posed inlet conditions. Simulations of a linear compressor cascade at a moderate Reynolds number was studied by Zaki et al [12] -the periodically passing wake caused the suction-side flow to separate and roll-up into discrete K-H vortices.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of small-scale turbulence embedded within the wakes was studied by Wissink et al [4], who concluded that while the large-scale motion of the wake triggers the Kelvin-Helmholtz (K-H) instability on the suction side of the blade, the small-scale disturbances embedded into the wake flow seed the transition to turbulence in the shear layer flow. Matsuura and Kato [5] used LES to predict transitional flow in a turbine cascade and found that the dominant unsteady behaviour of the transitional boundary layers depends upon the presence of simulated freestream turbulence.…”
Section: Introductionmentioning
confidence: 99%